Pulmonary involvement in multisystem inflammatory syndrome in children, a diagnostic conundrum: case series from a tertiary care hospital in eastern India - Roy, Santanu; Ghosh, Prakash Chandra; Bera, Mitali; Majumder, Sananda (International Journal of Contemporary Pediatrics, 2022)
In April 2020, a novel syndrome in children and adolescents, termed multisystem inflammatory syndrome in children (MIS-C), related to SARS-CoV-2 (severe acute respiratory syndrome corona virus 2) infection was first described in the United Kingdom and Italy. In this case series, we analysed 6 patients who had moderate to severe respiratory system manifestations at presentation, closely resembling the acute infection. A retrospective analysis of 6 pediatric patients, diagnosed as MIS-C, presenting with predominant respiratory system manifestations between December 2020 to October 2021 was undertaken. All the 6 patients presented with fever and predominant respiratory symptoms which mainly included difficulty in breathing, while two patients had accompanying chest pain. Gastrointestinal symptoms were found to be the most common accompanying systemic involvement. The inflammatory markers were found to be deranged in all the patients. COVID-19 RT-PCR was negative and serology for COVID-19 IgG was positive in all the patients. All the patients were successfully discharged. All were followed up 1 month after discharge. Residual respiratory morbidity was found in none of them. Our case series highlights the importance of distinguishing active covid-19 infection from MIS-C especially in the setting of overlapping clinical features. Timely diagnosis of MIS-C will also prevent unnecessary antibiotic usage.